Audit of Colorectal Cancer Histopathology Reports - Nasir, Humaira; Tariq, Naima; Nazir, Bisma; Bibi, Asifa; Anees, Rabia (International Journal of Pathology, 2018)
Objective: This audit was carried out principally to assess adherence of histopathological reporting ofcolorectal cancer cases at Shifa International Hospital (SIH), Islamabad to the College of AmericanPathologists (CAP) Protocol.Materials and Methods: The audit sample includes 100 cases of colorectal cancer identified via largebiopsies. The cases were retrospectively collected from 30-11- 2014 to 04-06-2012 using Oracle software. Reauditwas done from 01-06-2015 to 30-09-2015 and included 09 cases of colorectal cancer.Results: Out of a total of 9 macroscopic features specimen type was mentioned in 100% of reports. 3parameters (procedure, specimen length and tumor site) were mentioned in more than 90% reports.Macroscopic tumor perforation was mentioned in 84% reports and tumor size in 62% reports. Macroscopicintactness of mesorectum was mentioned in 87% of cases.Out of a total of 24 microscopic features histological tumor type was mentioned in 100% reports. Tumor grade,pathological stage and lymph node involvement was mentioned in more than 90% of reports. Status ofproximal and distal margin was given in 99% of reports; however status of radial margin was mentioned inonly 92% of reports. Features suggestive of microsatellite instability were mentioned in less than 20% of cases.Reaudit was carried out after an interval of 06 months which showed marked improvement.Conclusion: Audits play an important part in improving the quality of histopathological reporting.Continuous medical education and frequent audits should be imparted so that we as pathologists can learnfrom our mistakes and play proactive part in better patient management.